Annotated catalogue of Pakistani Acrididae (Orthoptera: Caelifera: Acridoidea) - Sultana, Riffat; Song, Hojun (Zootaxa, 2024)
An annotated catalogue of Acrididae (Orthoptera: Caelifera) of Pakistan and its two adjacent territories is presented. A total of 169 species (including subspecies) belonged to 66 genera and 29 tribes with 14 subfamilies are reported from this region. Oedipodinae (56) was the most species-rich subfamily, followed by Gomphocerinae (30), Acridinae (15), Calliptaminae with (12), Eyprepocnemidinae (12) Oxyinae (9), Hemiacridinae (10), Cyrtacanthacridinae (8), Catantopinae (7), Tropidopolinae and Teratodinae each with (3), Spathosterninae (2) and Coptacrinae, and Melanoplinae are represented by a single species. Pakistan harbors about 51.76% of the Acridomorpha species recorded for subtropical Asia, including 13.61% of the Caelifera, are endemic. Since the first checklist was published in 1990, which listed 39 species, hundreds of additional specimens from the region have been collected and databased, new species have been described, and the taxonomic status of some species has changed. Due to a lack of long-term studies for most localities, several species that were new at the time of collection are meanwhile described from other areas of Southeastern Asia. Specimen data from insect collections, databases, scientific literature, and unpublished records were compared to the original checklist. Our list includes three endemic species, 11 rare species, seven first-time reports, including five expected and 18 dubious records. Additionally, there are a few species from protected areas, although no consistent analysis has yet been done on species restricted to protected areas in Pakistan. A detailed account of subfamilies, endemic and rare species, and those anticipated to occur in Pakistan is also presented. This checklist provides baseline data for researchers and the public, strengthening the pest framework for management.